The impact of globalızatıon on culture and religion - ODABAŞI, FATMA (My University, 2022)
The paper consists of two main titles: In the first title, the concept of globalization will be emphasized and related theories in social theory will be included. In the second title, the impact of globalization on culture and religion will be discussed and examples from Turkey will be given. The study was created with a qualitative research design and document scanning technique was used. Globalization, which has become more visible with the revolutions in communication and information technologies, is a phenomenon that, in Giddens's words, points out that "increasingly, we live in a single world and we are becoming more dependent on each other as individuals, groups and nations". Theoretical approaches on the subject are generally included in the debates on whether the nation-state has lost its importance and are discussed under three headings as "hyperglobalizers", "sceptics" and "transformationalists". Globalization is an effective process in the cultural and religious field as well as in the economic field. It is possible to talk about two approaches in terms of the cultural dimension of globalization. The first approach sees globalization as a homogenizing process with a specific purpose. The second approach is that of sociologists, who consider globalization as a heterogenizing process in the sense of localizing the universal. The effect of globalization on religion is handled with a similar distinction, with two different approaches. The first is the approach that sees globalization as an opportunity and hope. The second is the approach that perceives globalization as a religious threat and is worried about it.
Küreselleşmenin kültür ve dine etkisi
Keywords: Globalization; globalization and culture; globalization and religion